Experimental and Applied Mechanics, Volume 6 Proceedings of the 2011 Annual Conference on Experimental and Applied Mechanics - Proulx, Tom (Conference Proceedings of the Society for Experimental Mechanics Series, 2011)
Experimental and Applied Mechanics represents one of eight volumes of technical papers presented at the Society for Experimental Mechanics Annual Conference & Exposition on Experimental and Applied Mechanics, held at Uncasville, Connecticut, June 13-16, 2011. The full set of proceedings also includes volumes on Dynamic Behavior of Materials, Mechanics of Biological Systems and Materials, Challenges in Mechanics of Time-Dependent Materials and Processes in Conventional and Multifunctional Materials, MEMS and Nanotechnology; Optical Measurements, Modeling and, Metrology; Experimental and Applied Mechanics, Thermomechanics and Infra-Red Imaging, and Engineering Applications of Residual Stress.